The Ten Virtues of an Academic - Hanwella, Raveen (Sri Lanka Journal of Psychiatry, 2015)
Hemamali Niranjala Perera joined the Faculty of Medicine as a lecturer in the Department of Psychiatry in 1986 and retired as Professor in Psychiatry in September 2014, after nearly three decades of service. In recognition of her services she was made Emeritus Professor of the University of Colombo. To my mind she has all the virtues of what an academic should be – an inspiration to all the younger members of this faculty. First she was fully committed to the task given. The child and adolescent unit, the pioneering such unit in Sri Lanka, started by Dr. Anula Nikapotha, was left in the doldrums after her sudden departure. Hemamali, after qualifying as an adult psychiatrist in the UK, was requested by Prof. Nalaka Mendis to take over the Unit. She took up the challenge and went to Australia to retrain as a child and adolescent psychiatrist. After her return to Sri Lanka she never looked back. She pioneered the day and inpatient hospital child psychiatry services of the Lady Ridgeway Hospital. With her initiation and leadership, tertiary care assessment and treatment centres were setup for children with autism, learning difficulties and behavioural problems, in addition to routine services. They were the first of its kind in the country. Second, she was a dedicated teacher of both undergraduates and postgraduates. She initiated major reforms in the teaching of child psychiatry to final year students. Due to her efforts the medical students from the Faculty of Medicine Colombo can be said to have the best child psychiatry-training program in the country, enabling them to become medical practitioners competent in managing child and adolescent problems. She played a significant role in setting up the specialist MD training in child psychiatry. Almost all the child psychiatrists practicing in the country today were trained by her. Third she was a researcher. At the time of retirement she had published 11 monographs and 58 articles in peer reviewed journals, presented 51 papers in national and international forums, been the resource person for numerous workshops and delivered the 2004 Sri Lanka College of Psychiatrists’ Oration. She was honoured with the Presidential Award for research on three occasions. She did not write her papers in isolation and always involved her team. On many occasions the papers submitted by her team won the best paper or poster award, no doubt giving great satisfaction and encouragement to the young doctors. Fourth, she made a significant contribution nationally and internationally in her field. Hemamali is a pioneer and leader in the field of autism in children. Early diagnosis and treatment is crucial to the successful treatment of this distressing condition. She developed ways to identify early the signs of autism in children and developed behavioural methods of treatment. This was long before more developed countries initiated such programs. Fifth, Hemamali was an academic who made her presence felt. Sadly there are academics who are neither seen nor heard during their career and fade away into retirement. She was not that kind of academic. She took an active part in the life of the medical faculty and was never cowed by authority. She was assertive when she had to be. This was rarely for herself, but always for the development of her field. Even the most formidable of Deans gave way when Hemamali made a request. Sixth, she was responsible. She took responsibility for her work, her trainees and students. She was never late for meetings, classes or examinations. Whenever she undertook a task she would deliver on time with the minimum of reminders. The work was always thorough and well written never slipshod or half-done. She ensured that her trainees got the best possible training posts abroad. Her reputation with her colleagues abroad ensured that her references always received a positive response. Many a consultant psychiatrist today owe their excellent overseas training posts to Hemamali. A little known but unpleasant task of a child psychiatrist is to appear in courts, to give evidence in child custody and child abuse cases. Such cases are often acrimonious and generate much hostility, and many child psychiatrists may be tempted to avoid such confrontations. Yet Hemamali did not shirk her responsibility. She was a formidable witness in courts and would not be browbeaten by lawyers. Once, having given evidence in a High Court, the Judge sent the Court Mudliyar to request her telephone number. It was not for a dinner date – rather, he had been so impressed with her that he wanted to refer a family member to her for professional help!